Effect of Remote Home Rehabilitation Mode on Children with Cerebral Palsy and Their Families during Epidemic Isolation - Tingting XU; Yunfei QIAO; Mao HUANG (康复学报)
Objective:To observe the effect of remote home rehabilitation mode on the development of children with cerebral palsy and their families'emotions during the quarantine for COVID-19.Methods:A total of 80 children with cerebral palsy(CP)who were treated in Children's rehabilitation department of Hebei Hospital of Traditional Chinese Medicine, the outpatient department from December 1, 2020 to January 5, 2021 were randomly divided into the control group and the observation group, with 40 cases in each group. The control group received routine home quarantine control and daily exercise training. Rehabilitation therapists used mobile phones or computer videos and other remote media platforms to carry out home isolation measures, community prevention and control measures, psychological counseling, dietary and feeding guidance and daily exercise guidance for CP children and their families. The exercise training content mainly refered to"exercise guidance and advice for children aged 0-6 years old during the epidemic of COVID-19", once a day, 30 minutes each time, five times a week, continuous intervention for one month. The observation group received remote home rehabilitation mode on the basis of prevention and control isolation at home, CP children's families trained their Children in movement, occupation, speech, cognition, massage at home under the remote guidance of rehabilitation therapists, once a day, 30 minutes a time, five times a week, continuous training for one month. Before and after intervention, Gesell scale was used to evaluate the growth and development of the children with CP; the clinical symptom score of traditional Chinese medicine(TCM)was used to evaluate clinical effect; weight scale was used to measure body mass; color doppler ultrasound was used to detecte cerebral hemodynamics indexes such as the cerebral artery mean arterial blood flow velocity(Vm)and vascular resistance index(RI); Hamilton depression scale(HAMD-17)was used to evaluate the depression of the CP children's family members.Results:Before intervention, there were no significant differences in DQ score, clinical symptom score of TCM, Vm, RI index, body mass and HAMD-17 score between two groups(P>0.05).Compare with before intervention, body weight, Vm and HAMD-17 scores of the two groups after intervention were significantly increased, DQ score of the observation group after intervention was significantly increased, the RI was significantly decreased, with statistically significant differences(P<0.05).Compared with the control group, DQ score and Vm of the observation group after intervention were significantly higher, while clinical symptom score of TCM, RI and HAMD-17 scores of the observation group after intervention were significantly lower, the difference was statistically significant(P<0.05).There was no significant difference in body mass between the two groups after intervention(P>0.05).Conclusion:Remote home rehabilitation mode can effectively promote the growth and development of CP children, improve the symptoms of tardiness in standing, walking, speaking, soft and hard hands and feet, and relieve the depression of CP children's family members, which is an effective rehabilitation training mode for CP children during the period of epidemic isolation.